A Facile Method to Control Pore Structure of PVDF/SiO2 Composite Membranes for Efficient Oil/Water Purification - Qianqian Xu (MDPI AG, 2021)
The use of poly(vinylidene fluoride) (PVDF) microfiltration (MF) membranes to purify oily water has received much attention. However, it is challenging to obtain high-performance PVDF microfiltration membranes due to severe surface fouling and rapid decline of permeability. This study explored a new approach to fabricate high-performance PVDF/silica (SiO2) composite membrane via the use of a polymer solution featuring lower critical solution temperature (LCST) characteristics and the non-solvent thermally induced phase separation method (NTIPS). Coupling with morphological observations, the membrane formation kinetics were analyzed in depth to understand the synergistic effect between the LCST solution properties and fabrication conditions in NTIPS. Utilizing such a synergistic effect, the transition from finger-like macrovoid pores to bi-continuous highly connected pores could be flexibly tuned by increasing the PVDF concentration and the weight ratio of SiO2/PVDF in the dope solution and by raising the coagulation temperature to above the LCST of the solution. The filtration experiments with surfactant-stabilized oil-water emulsion showed that the permeation flux of the PVDF/SiO2 composite membranes was higher than 318 L·m−2·h−1·bar−1 and the rejection above 99.2%. It was also shown that the PVDF/SiO2 composite membranes, especially those fabricated above the LCST, demonstrated better hydrophilicity, which resulted in significant enhancement in the anti-fouling properties for oil/water emulsion separation. Compared to the benchmark pure PVDF membrane in oily water purification, the optimal composite membrane T70 was demonstrated via the 3-cycle filtration experiments with a significantly improved flux recovery ratio (Frr) and minimal reduced irreversible fouling (Rir). Overall, with the developed method in this work, facile procedure to tune the membrane morphology and pore structure was demonstrated, resulting in high performance composite membranes suitable for oil/water emulsion separation.